Environmental Impact of Polymer Waste and its Recycling - Kulbasheva, X. X.; Fayziyeva, Sh. A.; Sodiqova , M. M. (Miasto Przyszłości, 2025)
Polymer waste causes great harm to the environment, as it does not decompose for a long time, polluting the soil, water and air. Plastic and other polymer materials undergo a slow biodegradation process, as a result of which they have a negative impact on ecosystems. Therefore, recycling processes are of great importance to solve the problems associated with polymer waste. Polymer recycling allows for the efficient use of their hidden resources and the protection of the environment.